2023
DOI: 10.3390/pathogens12091110
|View full text |Cite
|
Sign up to set email alerts
|

Periodontopathogens Porphyromonas gingivalis and Fusobacterium nucleatum and Their Roles in the Progression of Respiratory Diseases

Tao Shi,
Jiale Wang,
Jiajia Dong
et al.

Abstract: The intricate interplay between oral microbiota and the human host extends beyond the confines of the oral cavity, profoundly impacting the general health status. Both periodontal diseases and respiratory diseases show high prevalence worldwide and have a marked influence on the quality of life for the patients. Accumulating studies are establishing a compelling association between periodontal diseases and respiratory diseases. Here, in this review, we specifically focus on the key periodontal pathogenic bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 162 publications
0
4
0
Order By: Relevance
“…Studies have identified common pathogens between PD and COPD, including Porphyromonas gingivalis , Tannerella forsythia , Haemophilus, and Treponema denticola [ 39 ]. Among these, Porphyromonas gingivalis is closely linked to the development and progression of periodontal disease, being a gram-negative anaerobic bacterium commonly colonizing periodontal pockets [ 40 ]. Nan Feng et al found that it could migrate to the lungs, alter the pulmonary microbiota, and exacerbate chronic obstructive pulmonary disease (COPD) [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have identified common pathogens between PD and COPD, including Porphyromonas gingivalis , Tannerella forsythia , Haemophilus, and Treponema denticola [ 39 ]. Among these, Porphyromonas gingivalis is closely linked to the development and progression of periodontal disease, being a gram-negative anaerobic bacterium commonly colonizing periodontal pockets [ 40 ]. Nan Feng et al found that it could migrate to the lungs, alter the pulmonary microbiota, and exacerbate chronic obstructive pulmonary disease (COPD) [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, F. nucleatum was also detected in the lower respiratory tract specimen of patients with empyema and the pleural fluid of patients with lung abscess ( 81 ). Although the source of infection is unknown, F. nucleatum colonized in the oropharynx or periodontal pocket may be a source of lung infection in individuals who are prone to aspiration ( 87 ). These results indicate the potential role of F. nucleatum in respiratory diseases.…”
Section: Periodontal Pocket May Be a Potential Source Of Respiratory ...mentioning
confidence: 99%
“…The mRNA expression of IL -6 in HBFs inoculated with F. nucleatum was enhanced in all groups in this study. F. nucleatum strongly induced IL -6 production in bronchial epithelial cells, pharyngeal epithelial cells, and alveolar epithelial cells(52) . Our results are consisted with these studies.…”
mentioning
confidence: 91%